Solubilisation properties of phosphatidylcholine - Taylor, Patria Maria (Department of Molecular and Cell Biology, 2020)
The solubilisation of glucose and related sugars by thoroughly-purified phosphatidylcholine (lecithin) in benzene solution has been studied. The extent of solubilisation of the sugar has been found to depend on the concentration of lecithin, the structure of the sugar and the presence of cholesterol as a co-solute. The limiting solubility of glucose was achieved at low lecithin concentrations and corresponds to a 1:1 molar ratio of glucose to lecithin. Osmometric evidence indicated that, at higher concentrations, glucose was carried within the lecithin micelle. For other suiars, solubilisation was found to depend on the size of the sugar molecule relative to that of the lecithin micelle and on the number and acidity of its free hydroxyl groups. Enthalpy and entropy of solubilisation were determined for glucose and the results are consistent with an interaction mechanism involving hydrogen bonding via the free hydroxyl groups. Cholesterol, when present as a co-solute, competed for available hydrogen bonding sites on the lecithin molecule and thus decreased the amount of glucose solubilised, but in benzene solutions lecithin exhibited a 5:1 preference for glucose hydroxyl over cholesterol hydroxyl. In aqueous-ethanolic solutions inversion of the lecithin micelle occured and accordingly cholesterol could be solubilised. As the dielectric constant of the medium was decreased by the addition of ethanol, the micellar weight decreased and the uptake of cholesterol increased. In 90% ethanol the limiting solubility of cholesterol corresponded to a 1:1 cholesterol/lecithin ratio. In 70% ethanol the uptake of cholesterol corresponded to a 1:9 cholesterol/lecithin ratio, and this ratio was independent of lecithin concentration below 7.0 mg/ml. In media of higher dielectric constant lecithin formed an opalescent sol rather than a solution and the uptake of cholesterol decreased further, but the cholesterol/lecithin molar ratio continued to be independent of the lecithin concentration of the sol. In none of the aqueous solutions was glucose found to have any effect on the uptake of cholesterol. It is possible that these results may have biological significance.